Personal financial literacy is at the heart of business planning ("Journal "U". Economy. Management. Finance.", 2024)
The article presents a correlation between the items of the personal budget and the production budget, highlighting the importance of the ability to manage personal finances as the basis for the correct approach to the finances of an enterprise.
Keywords: budget items; personal financial literacy; production budget; personal income and expenses